Inovasi Pembuatan Pengharum Ruangan dengan Peppermint (Mentha Piperita) sebagai Pengusir Lalat (Diptera) dan Rayap (Isoptera) - Abimanyu Abdul Aziz; Nurul Hidayati; Agus Widayoko (SMA Trensains Muhammadiyah Sragen, 2025)
This study aims to test the effectiveness of mint leaf air freshener in reducing the number of termites and flies. Mint leaves have many health benefits. Mint leaves (Mentha Piperita L.) are often used as breath fresheners such as mouthwash, candy, or toothpaste. The main elements of mint leaves are essential oils, menthol and menthone. Mint leaves have a fragrant aroma and a refreshing cool taste because of the essential oil content in menthol oil. There are two formulas that were tested, namely F1 with the addition of alcohol and F2 with the addition of alcohol and peppermint oil. The laboratory tests carried out were organoleptic tests, specific gravity tests, endurance tests and user preference tests. Based on the organoleptic test, F2 is better than F1. From the specific gravity test, F1 is higher than F2. Based on the endurance test, F2 has a longer durability than F1. Based on the preference test, F2 has the potential to be preferred by users. A more specific explanation of the research findings can be done by comparing the results of this research with other relevant research, or other products that have the same basic ingredients and functions.